Descriptions of two new species of Gonatocerus (Hymenoptera: Mymaridae) from southeastern Europe - Triapitsyn, Serguei V.; Donev, Atanas D.; Huber, John T. (Zootaxa, 2013)
Two new taxa, Gonatocerus (Lymaenon) bulgaricus Donev & Triapitsyn (Bulgaria, and also apparently mainland Greece) and G. (Lymaenon) mediterraneus Donev & Triapitsyn (Greece—Crete Island) are described, diagnosed, and illustrated. Also, a species tentatively identified as G. (Lymaenon) ?beshbarmak Triapitsyn is reported from mainland Greece. If the species is indeed G. beshbarmak then this is the first record of it from Greece.